Tanzania’s agrifood system structure and drivers of transformation - Benfica, Rui; Diao, Xinshen; Pauw, Karl; Randriamamonjy, Josee; Thurlow, James; Ellis, Mia (International Food Policy Research Institute, 2023)
Tanzania experienced strong annual economic growth of 6.2 percent between 2009 and 2019 (NBS 2020). Despite the country’s relatively less restrictive domestic COVID-19 measures, the adverse effects of the global commodity market disruptions during the pandemic led to a slowdown in GDP growth to 4.8 percent in 2020 and 4.9 percent in 2021 (NBS 2021). Growth is expected to reach 5.3 percent in 2023 and 6.1 percent in 2024 (World Bank 2023), suggesting that Tanzania is returning to its pre-pandemic growth trajectory. While the economy has been going through a process of structural transformation with rapid growth, agriculture continues to play an important role in both output and employment, accounting for about 30 percent of total GDP and 70 percent of employment in 2019. The agriculture sector performed well over the pre-pandemic decade, with agricultural growth accelerating from 3.8 percent per year in the 2009–2014 period to 5 percent in the 2014–2019 period (NBS 2020). The agriculture sector has also been playing an important role in weathering the global commodity market shocks in 2022 and 2023, thanks to some export crops that benefit from the negative terms of trade shock (Diao and Thurlow 2023). In this brief, we unpack the historical and projected economic growth trajectory further to better understand the role of agriculture as well as the broader agrifood system (AFS) in the performance and transformation of the economy of Tanzania.